Neuromuscular function, hormonal and redox status and muscle damage of professional soccer players after a high-level competitive match - Silva, J. R.; Ascensão, A.; Marques, F.; Seabra, A.; Rebelo, A.; Magalhaes, J. (European Journal of Applied Physiology, 2013)
The main aim was to analyse the impact of an official match on hormonal and redox status, muscle damage and inflammation and neuromuscular function. Seven high-level male soccer players from the same team performed an official match and data were collected 72 h before, 24, 48 and 72 h post-match. Plasma testosterone/cortisol ratio (T/C), creatine kinase (CK), superoxide dismutase (SOD), glutathione peroxidase (GPX) and reductase (GR) activities, myoglobin (Mb), C-reactive protein (CRP), uric acid (UA), protein sulfhydryls (-SH), malondialdehyde (MDA) concentrations and total antioxidant status (TAS) were measured. Sprint, jump and change of direction performance, and maximal isokinetic knee extension and flexion were obtained as neuromuscular functional parameters. Cortisol increased and T/C decreased until 48 h recovery (P < 0.05). Mb, CRP and -SH (P < 0.05) increased at 24 h and CK, TAS, SOD and MDA (P < 0.05) increased up to 48 h recovery. GR increased and GPX decreased at 24 h recovery (P < 0.05). Jump performance decreased 24 h post-match (P < 0.05), but no significant alterations in sprint, change of direction and muscle strength were observed. In conclusion, an official match resulted in changes in plasma biomarkers until 48 h of recovery period, without major impact on performance.